2022
DOI: 10.3329/bjas.v51i2.60493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moisture content on the quality of vermicompost produced from cattle manure

Abstract: This research aimed to evaluate the quality of vermicompost produced from cattle manure at different levels of moisture content. For this purpose, cattle manure containing different moisture content such as 60% moisture (T1), 70% moisture (T2) and 80% moisture (T3) treatments were adopted with 3 replications. A total of 9 vermicomposting pits were filled with 25 kg of cattle manure, each having the same amount of red worms. Parameters studied were dry matter (DM), crude fibre (CF), crude protein (CP), ether ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Liang et al (2003) investigated the effect of moisture content on the compost microbial activity during the biodeterioration of sludges. Hossen et al (2022) found that an initial moisture content of 70% was suitable for an efficient vermicomposting. Another study reported the influence of moisture content variation on the kinetic reaction rate of vermicomposting.…”
Section: Compostingmentioning
confidence: 99%
“…Liang et al (2003) investigated the effect of moisture content on the compost microbial activity during the biodeterioration of sludges. Hossen et al (2022) found that an initial moisture content of 70% was suitable for an efficient vermicomposting. Another study reported the influence of moisture content variation on the kinetic reaction rate of vermicomposting.…”
Section: Compostingmentioning
confidence: 99%